Analysis of inclined slot-loaded patch for dual-band operation - Shivnarayan; Vishvakarma B.R. (My University, 2025)
The theoretical analysis of a single feed inclined slot-loaded rectangular microstrip patch antenna is presented using modal expansion cavity model and circuit theory concept. By cutting the inclined slot along the radiating edge of the patch, a dual-frequency operation is obtained. The input impedance, VSWR, and return loss are calculated. It is found that the frequency ratio of two resonant frequencies can he varied from 1.92 to 2.44 by the inclination angle of the slot. The theoretical results are validated by experimental results. © 2006 Wiley Periodicals, Inc.